The Development Of Assesssment Instrument For Religious Moderation Literacy In Madrasah Ibtidaiyah - Rofiah, Siti; Jasminto, Jasminto (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
Religious literacy and religious moderation have become very important topics to be studied since the emergence of religious extremism and radicalism which has the potential to cause religious disharmony. This is influenced by the individual's religious understanding which is also related to the individual's ability to absorb information and understand religious facts in a social context. To find this out, peril is designed an assessment instrument. This study aims to 1) Develop a literacy assessment of religious moderation as an effort to measure the extent to which students and teachers are literate in terms of religious moderation. 2) Determine the validity of the assessment instrument. This research is a development research using the Plomp model which consists of 4 stages, namely the initial assessment stage, the design stage, the construction stage and the test stage, evaluation and revision. The assessment instrument was validated by 3 expert judgments with the subject of the trial being 20 students and 10 teachers at MI Al Ittihad Jogoroto Jombang. The wide-scale trial was 45 upper-class students of MI Al Ittihad. The product of this research is an assessment instrument in the form of questionnaires and tests. The results of the development show that the average validity and reliability indicate high criteria and are appropriate to be used to measure religious moderation literacy at the madrasah ibtidaiyah level.   Keywords: Instrument Development, Asessment, Religious Moderation Literacy